Bacteria associated with truffle‐fruiting bodies contribute to truffle aroma. (9th July 2014) - Splivallo, Richard; Deveau, Aurélie; Valdez, Nayuf; Kirchhoff, Nina; Frey‐Klett, Pascale; Karlovsky, Petr
Summary: Truffles, symbiotic fungi renown for the captivating aroma of their fruiting bodies, are colonized by a complex bacterial community of unknown function. We characterized the bacterial community of the white truffle T uber borchii and tested the involvement of its microbiome in the production of sulphur‐containing volatiles. We found that sulphur‐containing volatiles such as thiophene derivatives, characteristic of T . borchii fruiting bodies, resulted from the biotransformation of non‐volatile precursor(s) into volatile compounds by bacteria. The bacterial community of T . borchii was dominated by α‐ and β‐ P roteobacteria . Interestingly, all bacteria phyla/classes tested in this study were able to produce thiophene volatiles from T . borchii fruiting body extract, irrespective of their isolation source (truffle or other sources). This indicates that the ability to produce thiophene volatiles might be widespread among bacteria and possibly linked to primary metabolism. Treatment of fruiting bodies with antibacterial agents fully suppressed the production of thiophene volatiles while fungicides had no inhibitory effect. This suggests that during the sexual stage of truffles, thiophene volatiles are exclusively synthesized by bacteria and not by the truffle. At this stage, the origin of thiophenes precursor in T . borchii remains elusive and the involvement of yeasts or other bacteria cannot be excluded.